The Relationship between Employee Involvement and Workplace Dispute Resolution - Colvin, Alexander (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 2004)
This paper examines the relationship between employee involvement programs and workplace dispute resolution using data from the Workplace and Employee Survey (WES) conducted by Statistics Canada. The results provide support for a link between employee involvement and lower grievance rates in unionized workplaces. This link existed for establishments in both the goods and service sectors, but the practices involved differed between industrial sectors. By contrast, in nonunion workplaces, results of the analysis provided support for a link between the adoption of employee involvement programs and formal grievance procedures, but not between employee involvement and lower grievance rates.